Assessing the impact resistance and damage tolerance of aluminium composite fibre metal laminates under low velocity impact test - Mohd Fadhil, Rani; Mohd Ruzaimi, Mat Rejab; Norhaida, Ab Razak; M. I., Ibrahim; M. Z., Azir; Z., Zaulkafilai (Faculty Mechanical Engineering, UMP, 2025)
The automotive industry requires materials that are light in weight to enhance fuel efficiency while optimizing safety standards alongside having a high impact resistance to improve the vehicle's overall safety features. This study focuses on evaluating the low velocity impact performance of fibre metal laminates (FMLs) with different configurations to identify the most suitable crash resistant structures for vehicles. Five FML configurations were fabricated using 2024-T3 aluminum with CFRP (B2), GFRP (B1), SRPP (B3) and hybrid combinations consist of CFRP-GFRP (B4) and SRPP-GFRP (B5) in 3/2 layered structures that were tested under low-velocity impact at 2.7-4.5 m/s using drop-weight testing with force, displacement and energy absorption measurements. B5 recorded the highest impact force of 13827.1 N due to the synergistic bonding of thermoplastic SRPP and the GFRP layer. B1 exhibited the best energy absorption of 86.4 J outperforming other configurations by 10% because of the glass fibre's strain-to-failure characteristics which allows for significant plastic deformation. B2 lagged in both energy absorption and force at 78.5 J and 11476.2 N respectively due to the brittleness of the carbon fibre. The ranking for energy absorption was B1 > B4 > B2 > B5 > B3 with all configurations showing proportional increases in strength with velocity. Configuration B5 composed of hybrid SRPP-GFRP demonstrated the best impact resistance outperforming CFRP systems by 20.5% in force resistance, while GFRP-based FMLs (B1) showed better energy absorption at 86.4 J which is critical for managing crash energy thus illustrating that the selection of materials relies on the designated zone of an automobile meant to endure a collision, prioritizing either force resistance or energy dissipation.